2023
DOI: 10.1021/acs.jafc.3c00524
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Gut-Specific Carboxylesterase SlCOE030 in Polyphagous Pests of Spodoptera litura Conferring Tolerance between Nicotine and Cyantraniliprole

Abstract: Insecticides tolerance in herbivorous arthropods is associated with preadaptation to host plant allelochemicals. However, how plant secondary metabolites activate detoxifying metabolic genes to develop tolerance remains unclear. Herein, the tolerance of Spodoptera litura larvae to cyantraniliprole was increased after nicotine exposure. An S. litura α esterase, SlCOE030, was predominantly expressed in the midgut and induced after exposure to cyantraniliprole, nicotine, and cyantraniliprole plus nicotine. Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
(148 reference statements)
1
14
0
Order By: Relevance
“…To obtain more insights into CYP3- and CYP4-mediated cyantraniliprole tolerance, homology modeling and molecular docking were conducted, which are methods that have been used to provide evidence for the protein involvement in insecticide detoxification. ,,, In this study, SlCYP332A1 , SlCYP6AB12 , SlCYP6AB59 , SlCYP6AN4, and SlCYP340A were selected to perform homology modeling and molecular docking. The results showed that the binding energy between these five P450s and cyantraniliprole ranged from −5.10 to −6.87 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To obtain more insights into CYP3- and CYP4-mediated cyantraniliprole tolerance, homology modeling and molecular docking were conducted, which are methods that have been used to provide evidence for the protein involvement in insecticide detoxification. ,,, In this study, SlCYP332A1 , SlCYP6AB12 , SlCYP6AB59 , SlCYP6AN4, and SlCYP340A were selected to perform homology modeling and molecular docking. The results showed that the binding energy between these five P450s and cyantraniliprole ranged from −5.10 to −6.87 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…The S. litura population was purchased from the Institute of Plant Protection, Academy of Agricultural Sciences of Jilin Province in July 2019, and the larvae and adults were reared under the same conditions which were described in our previous study. 27 All S. litura samples were maintained in our insect garden without any insecticide exposure.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of the bioassays used are provided in our previous study. 31 The median lethal dose (LD 50 ) and 95% fiducial limits were calculated by probit analysis using SPSS Statistics (IBM SPSS Statistics 26 software, Chicago, IL, USA) and PoloPlus 2.00 software (LeOra Software, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%